Carbon nanotubes supported Pt-Co-P ultrafine nanoparticle electrocatalysts with superior activity and stability for methanol electro-oxidation. (10th October 2016) - Sun, Junting; Dou, Meiling; Zhang, Zhengping; Ji, Jing; Wang, Feng
Abstract: The Pt-Co-P ultrafine nanoparticles supported on carbon nanotubes (Pt-Co-P/CNT) have been successfully synthesized by a hypophosphite-assisted one-pot reduction strategy and used as the electrocatalysts for methanol oxidation reaction (MOR). Transmission electron microscope observation clearly indicates that the Pt-Co-P nanoparticles are highly dispersed onto the surface of CNT with a narrow particle size distribution. The average diameter of the Pt-Co-P nanoparticles with the different P contents can be controlled from 1.5 nm to 2.7 nm, probably by the assistance of in-situ phosphate capping agent for nanoparticle growth, which generated from simultaneous oxidation of sodium hypophosphite. The electrochemical measurement data indicate that the Pt-Co-P/CNT with the average particle diameter of 1.5 nm possesses superior electrocatalytic activity, outstanding tolerance against CO-like intermediates and excellent electrochemical stability, which is better than those of Pt-Co/CNT and commercial Pt/C. The improved electrochemical performance of Pt-Co-P/CNT can be attributed to the high electrochemical active surface area and rapid removal of CO-like intermediates arising from the ultrafine features of Pt-Co-P nanoparticles as well as the strong interaction among Pt, Co, and P. Therefore, the Pt-Co-P/CNT electrocatalysts prepared by a hypophosphite-assisted one-pot reduction strategy can be considered as a promising candidate for high performance MOR electrocatalyst.